Modul “Gen Positif” untuk Meningkatkan Pengetahuan Regulasi Emosi Takut Gagal Siswa Remaja Awal - Astiti Tenriawaru Ahmad; Asmadi Alsa (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2017)
Early adolescents need adaptation in various aspects including in the process of achievement of academic achievement. The difficulties encountered in achieving goals in the academic field caused early adolescents to develop a fear of failure. Individuals will try to avoid failure by determining their goals far below its potential, feel anxious, and not motivated in learning. This emotion can be a serious problem if it is not regulated in an adaptive way. Therefore early adolescents need knowledge of how to regulate the emotions of fear of failure. This study aims to validate the module "Gen Positif" (Generasi terampil mengolah emosi dan Aktif berprestasi) and find out how far the increase in knowledge and ability of emotional regulation of fear of failure in early adolescents. The study design used untreated control group designs with dependent pretest and posttest samples. Research participants as many as 12 early adolescents. The analysis of the study was conducted by comparing the scores of emotional regulation knowledge before and after manipulation was given. The results show that the module "Gen Positif" is valid content and empirical.